(untitled) (Research, Society and Development, 2022)
The Right to Education is a human, constitutional, social and fundamental right. Brazil has always faced issues of Law regarding equality and equity of access to and opportunities in Education and with the pandemic and its impacts on this constituted right, existing inequalities have worsened and are thematic for discussions and debates in all social spheres. That said, the present study is justified by the need for discussions on the subject and aims to analyze the impacts of the pandemic on the Right to Education, resulting in greater and worse inequalities. For this purpose, a bibliographic research of an exploratory and descriptive character was used. The resulting production is divided into four titles, namely: From the Right to Education, The COVID-19 pandemic, The right to education in Brazil – the pre-pandemic scenario, The impacts of the COVID-19 Pandemic on the Right to Education, a universe of inequalities. The author’s impressions and conclusions constitute the Final Considerations.